Evaluation of chronic headache by computed tomography: a retrospective study - Subedee, Anish (Journal of Nobel Medical College, 2012)
Objective: To find out the proportion of intracranial abnormalities in patients with chronic headache without neurologic abnormality with the use of computed tomography (CT) and to compare the results with similar studies done previously. Materials and methods: CT images of 56 patients with chronic/recurrent headache and normal neurological findings were reviewed retrospectively. In 38 of 56 patients, both plain and contrast enhanced CT were done. Patients were divided into three groups according to the CT findings: those with no abnormality, those with minor abnormality (that did not alter patient management) and those with clinically significant abnormality. Proportion of patients in each group was found out and results were compared with previous studies with similar study design. Z test was used to evaluate whether the difference in proportions of patients in our study and previous study was statistically significant or not. Results: Of the 56 patients, 50 had normal CT (89.28 %), four had minor abnormality (7.14%) that did not alter patient management and two had significant lesions (3.57%). Contrast enhanced CT did not improve lesion detection. The minor findings detected were sub-ependymal calcifications of Tuberous sclerosis, calcified neurocysticercosis and old lacunar infarctions in external capsule. Clinically significant lesions detected were small ring enhancing lesion (neurocysticercosis or tuberculoma) and pineal cyst. Results of this study were compared with previous study with similar study design. The Z test showed that the difference in proportions in these studies was not statistically significant (p =0.0708 for minor findings and p =0.2033 for significant findings). Conclusion: The proportion of intracranial abnormalities detected by CT in this study was similar to that of previous studies. The use of intravenous contrast material administration did not improve its yield. This corroborates the evidence that the ability of CT scan in detecting significant intracranial pathology is poor in patients with chronic headache without neurologic abnormality. DOI: http://dx.doi.org/10.3126/jonmc.v1i2.7301 Journal of Nobel Medical College (2012), Vol.1 No.2 p.57-63